Aprender a investigar investigando. Realización de una propuesta de formación - Sánchez-Robayo, Brigitte Johana; Torres-Duarte, José (Revista Científica, 2017)
This article reports a research which shows the most important design and application elements of a training proposal. This proposal allowed math teachers learnt about research through researching. The methodology was action research and the data were analyzed by means of participant observations, interviews and writings. The research validates a educative proposal in research which regards teachers as main authors of their professional knowledge building, recognizes the complexity or math teachers practice, improves critical views about the daily job and its objectives, considers the collaborative work as teachers mediation tool, raises changes about research conceptions and enables transformations of practice.